An Influence of Oil Prices and Inflation on Stock Price at Crude Oils Corp in 2012-2021 - Andriyani Hapsari; Luthfia Nurul Khumaidah (Sultan Publisher, 2025)
The research aims to find out and empirical evidence whether the oil price and inflation affects the stock price at Crude Oils Corp. in 2012-2021 as simultaneously and partially. This study uses quantitative methodology, with causality type. The sample used includes data from 2012 to 2021 on oil prices, inflation, and stock market at crude oils Corp. Data analysis uses multiple linear regression techniques with the support of IBM SPSS Ver25 program. In this study, the proceeds is reinforced by the results of the joint test of the two variables producing significance and also a strong contribution to the variable with a determination score of 79.3 percent. The highest influence on stock prices at Crude Oils Corp. is the inflation variable with a t-count of 5,524 while the oil price variable only produces a t-count of 2,627. Both variables above have significant positive results from the proceeds of the regression test. Companies can make policies when facing falling oil prices so that companies can still make a profit, then potential investors should use other information that can be used as a reference in making investment decisions, especially about Stock Price of Crude Oils.